(untitled) (Semiárida, 2020)
The objective was determine the effect of cover crops on the water use efficiency and total yield of the pumpkin crop. The study was carried out on a soil called petrocalcic Paleustoll, located in the south of the rugged plain of the semiarid Pampa region. In the same lot for three consecutive seasons, Rye (C) and rye + vetch (CV) were sown and fallow was established without cover cultivation. In this way, 6 management treatments for pumpkin cultivation were established: T1: without CC predecessor, with tillage prior to pumpkin planting, and without weed control during the pumpkin cycle. T 2: without predecessor CC with tillage prior to planting the pumpkin, with weed control (tillage and herbicide), during the pumpkin cycle. C H: Rye ancestor used as CC, with growth arrest by herbicide. C R: Rye ancestor used as CC, with growth arrest by rolling. CV H: Rye + Vetch ancestor used as CC, with growth arrest by herbicide. CV R: Rye + Vetch ancestor used as CC, with growth arrest by rolling. The results showed that on average in the 3 seasons C was higher than C V, in 22, 19 and 6% with respect to the total biomass, for the first, second and third seasons, respectively. Cover crops had higher fallow efficiency with respect to treatments without prior CC (T1 and T2). The highest pumpkin yields were over the CC, these being the ones with the lowest UC and the highest EUAt.